Is planet earth as a whole likely to be wage-led? - Arslan Razmi (University of Massachusetts, Department of Economics, 2017)
Evidence regarding the relationship between distribution, demand, and growth in the short run has been mixed. Open economy models that create the possibility of "beggar-thy-neighbor" growth offer one theoretical explanation for why this may be expected. Several authors have argued recently, however, that even if demand and growth are profit-led in many individual countries, the global economy is likely to be wage-led since the planet as a whole runs balanced trade. This paper finds that this argument, although intuitively appealing, does not hold up to careful examination. Although the world economy as a whole is a closed system, it is not isomorphic to a closed economy, thanks to repercussion effects, relative price movements, and cross-country heterogeneity. The effects of global redistribution depend on the nature of its constituent economies.
Keywords: F43; O41; O11; E12; 330; Demand regime; income distribution; wage-led growth; neo-Kaleckian open economy models